Legalidad, moralidad y cambio social (Scripta Theologica, 2018)
Before entering directly into his study, the author reflects on the theological perspective of civil laws. He underlines their connection with the end of man and points out that vigour and power is confered on human laws by their conformity with divine wisdom and will. Civil laws, however, have to take into account the social situation which they regulate. It can be said, in a certain sense, that the social reality produces, sustains and shapes law.In keeping with the rhythm of social change, positive law has also undergone changes. Every social change brings with it juridical change: the ordinance echoes the change and reflects it. The reverse is also true: new civil laws are the channel through which new models of conduct penetrate into society and spread.Among the multiple factors which have a role in the genesis and transformation of human positive law one finds a group of ideological stances and axiological representations. The root of the discrepancy is the acceptance of the law of God as the ultimate foundation of all human legality. It is basically a question of ethical objectivism and moral relativism or historicism. From a theological viewpoint, the two factors which indicate the criterion to be followed in the correct formulation of civil laws are: dynamic adjustment to the specific and changing needs of society at each moment oi history and adjustment to the permanent requirements of what ought to be according to superior principles which guarantee respect for the true nature and the transcendent meaning of man's life.The phenomenon of the mutual correlation between civil law and ethical guidelines is to be found always, but with this difference: from the point of view of natural and christian ethics, both the inspiration and evaluation of civil law always requires a clear distinction between legality and morality, between what is licit civily and what is licit morally; on the contrary, from a positivistic standpoint, that is from the point of view of moral relativism, it is man who sets the direction for his own conduct. What is moral and immoral, what is licit and illicit, is what man thinks it to be at a given moment in history. Ana in order to avoid the judgment of reprobation which accompanies transgression of the rule in cases of unlawful behaviour, an attempt is made to raise legality to the level of moral criterion. The author continues analysing the reelection in civil law of the contemporary crisis: the loss of the sense of objective morality is a reelection of the crisis of morality; the elimination of christian values in public life is a result of neglecting to consider the transcendental end of man in the formulation of civil law. Prof. Fuenmayor then deals with permisivity, whose ethic inspiration caused our time undergone a moral crisis which has effectively influenced civil laws. Finally he refers to tolerance, understood in the catholic sense, which, is nothing other than the application of prudence to the formulation of juridical norms according to the requirements of the common good. Consequently, he re-emphasises that the christian minority should aspire to be a majority and so recover the lead in the reform of civil law.